Adoption of Social Commerce and Live Streaming Selling in MSMEs: An Analysis of Success Factors in the Era of TikTok and Instagram - Irfan Azis (Return : Study of Management, Economic and Bussines, 2025)
Digital transformation has changed the business landscape of MSMEs in Indonesia, with social commerce and live streaming selling on platforms such as TikTok and Instagram becoming game-changers. However, only a small percentage of MSMEs have succeeded in adopting it optimally, so a deep understanding of the factors for the success of the adoption is needed. This study aims to analyze the factors of success in the adoption of social commerce and live streaming selling in Indonesian MSMEs, as well as compare implementation strategies on the TikTok and Instagram platforms. This study uses a qualitative approach with phenomenological design through a multi-case study. Data was collected from in-depth interviews, participatory observations, and document analysis of 23 MSMEs that actively use live streaming. The success of adoption is determined by the interaction of technology factors (ease and benefits of the platform), organization (commitment and readiness of human resources), individuals (entrepreneurial orientation), and trust-building strategies through real-time interaction, authenticity, and after-sales service. TikTok is more optimal for mass-market products with impulse purchases, while Instagram is effective for premium product branding. The research findings provide implementation guidance for MSMEs, input on feature development for platform providers, and policy recommendations for the government to support the inclusive digital transformation of MSMEs.